اسد محمد خان کی خاکہ نگاری کا تجزیاتی مطالعہ: An Analysis of Asad Muhammad Khan's Sketch writing (Khairulummah, 2022)
Asad Muhammad Khan is an important name in the world of Urdu fiction. He has made his mark in Urdu poetry, especially in lyricism. Apart from this, he is also an excellent sketch-writer. In "Yadeen: Guzri Sadi K Dost" he has received praise from the literati by presenting successful sketches of his friends. His sketches are literary and standard in every way. Like a master sketcher, Asad Muhammad Khan kept all the principles of sketch writing in mind and made his sketches interesting with the charm and elegance of the style. Asad Muhammad Khan also used satire in his sketches but with moderation and balance. He added his name to the list of sketch-writers by creating excellent sketches like "Mahalwali Nanna", "Jahangir Quarters ka Oracle", "Khwaja Sigparast" and "Portrait". In these sketches, he made these personalities alive. He highlighted the salient and representative aspects of these personalities without going into unnecessary details. In these hand-picked incidents he narrated only those incidents in which he can illustrate the personality traits in more vivid colors. Apart from this, he has also made an excellent addition to the memoir by mentioning some of his past friends. All in all, he is a masterful and skilled sketch-writer.